Case report : abortus with malaria falciparum in pregnancy - Didik Suhendro (Science Midwifery, 2023)
Malaria infection is still a global health problem. Malaria can affect all groups including pregnant women. Malaria infection in pregnant women can cause various dangerous complications, one of which is abortion. A 35-year-old pregnant woman was diagnosed with G6P5A0H5 uk 8-9 weeks with falciparum malaria. The patient was given Dihydroartemisin and piperacuine phosphate (DHP) therapy and symptomatic drugs. During observation the patient had no additional complaints and slowly returned to normal. One week later the patient experienced bleeding from the birth canal and was declared an abortion. There are several things that must be considered in the management of malaria in pregnant women such as resources, facilities and infrastructure available at first-level health facilities, and various matters regarding optimal maternal and fetal supervision so as to prevent various complications caused by malaria infection.